EXEMPLA OF IACOBUS DE VITRIACO AND HIS PREACHING ACTIVITY (Південний архів (історичні науки), 2025)
The article comprehensively examines the figure of Jacobus de Vitriaco (Jacques de Vitry) – a prominent French preacher, historian, and church leader of the ХII–ХIII century.The aim of the research is to highlight the biography and preaching activity of Jacobus de Vitriaco through the analysis of various historical sources, including the collection Sermones Vulgares.The methodological foundation of the article rests on general scientific principles of historicism, objectivity, and systematization, as well as on special historical methods such as the historical-typological, problem-chronological, problem-historiographical, and comparative-historical approaches. The study also applies various source-critical techniques for analyzing medieval historical monuments. Through the biographical method, the examination of the life strategies of a prominent clergyman is connected to his worldview, social background, and the broader circumstances that shaped his successful career as a cardinal. Hermeneutic and semiotic approaches enable a qualitative microhistorical analysis of the text. Finally, the deconstruction of selected exempla by Jacobus de Vitriaco helps to identify subconscious linguistic clichés which, together with other verbal formulas and recurring metaphors, demonstrate the repetitive structure of his sermons.Scientific novelty. The article highlights the outstanding role of Jacobus de Vitriaco’s preaching practice in organizing the Crusades and clarifies the significance of exempla in the religious and cultural life of Western Europe in the 12th–13th centuries. It demonstrates that his sermons served as an important medium for spreading the idea of the necessity of the Crusades. It traces the interrelation between personal motives, social and religious ideas, and life circumstances that led him to dedicate himself to missionary work. For the first time, Jacobus de Vitriaco’s exempla are examined through the lens of the so-called history of emotions. The study outlines prospects for further research into Jacobus de Vitriaco’s preaching activity and writings.Conclusions. The authors identified the main stages of Jacques de Vitry’s preaching activity and the specific features of his works, analyzing the peculiarities of medieval exempla as sources – their didactic function, personal, social, and religious motivations – as well as the ways emotions such as fear, anger, shame, and irritation were expressed in connection with moral principles and theological symbolism. The study also considers the relationship between the artistic techniques of a high-ranking cleric, his personal life experience, and the objectives of the Crusades. Jacques de Vitry’s exempla played a significant role in the religious and cultural life of High Medieval Western Europe. The text illustrates how, through vivid and accessible language, the author combined everyday realities with universal moral categories. It concludes that Jacques de Vitry’s exempla not only reflect the spiritual and moral condition of medieval society but also reveal the enduring patterns of human behavior common to different historical epochs.
Keywords: Jacobus de Vitriaco, Sermones Vulgares, exemplum, medieval literature, sermon, High Middle Ages, missionary work, moral, history of emotions, Christian culture, Crusades